2003
DOI: 10.2169/internalmedicine.42.490
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Serum Anti-ganglioside Antibodies by Latex Agglutination Assay in Guillain-Barre Syndrome: Comparison with ELISA

Abstract: Objective Rapid detection of serum anti-ganglioside antibodies in Guillain-Barre syndrome (GBS) could facilitate early diagnosis and early initiation of treatment, which might shorten the term of illness and reduce sequelae. Weexaminedserum anti-ganglioside antibodies in patients with GBSusing the latex agglutination assay developed by Alaedini and Latov (J Immunoassay 21:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Besides, the profile of different ganglioside autoantibodies in GBS was reported to vary depending upon the technique used. [ 29 30 31 32 ] Various studies have employed different types of immunoassays in profiling antiganglioside autoantibodies. Therefore, more precise information is required to explain the methodical and ethnic differences in anti-ganglioside and anti-GSC antibodies in GBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the profile of different ganglioside autoantibodies in GBS was reported to vary depending upon the technique used. [ 29 30 31 32 ] Various studies have employed different types of immunoassays in profiling antiganglioside autoantibodies. Therefore, more precise information is required to explain the methodical and ethnic differences in anti-ganglioside and anti-GSC antibodies in GBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods include line immunoassay, agglutination immunoassay, and glycol-array (12), and so on. The positive rate for agglutination immunoassay was 24% (13). Thin layer chromatography is considered to be the gold standard, but it is often unavailable for routine diagnostics (14).…”
Section: Discussionmentioning
confidence: 99%
“…Alaedini and Latov reported the latex agglutination assay for detection of anti-ganglioside antibodies (15). In this issue, Irie et al reported the results of antiganglioside antibody assay by the use of the above method with some modifications and compared the results with those of ELISA (16).…”
mentioning
confidence: 99%